Treatment acceptance and its associated determinants in cancer patients: A systematic review - Novirianthy, Rima; Syukri, Maimun; Gondhowiardjo, Soehartati; Suhanda, Rachmad; Mawarpury, Marty; Pranata, Agung; Renaldi, Teuku (Narra J, 2023)
Treatment recommendations for cancer patients are carried out according to clinical assessment, type and stage of cancer and treatment guidelines. However, many patients do not accept the recommendations. This raises obstacles in managing of cancers, which not only affects the patients, but also the family and people around the patients. This problem could increase morbidity, mortality and recurrence rate, which might result in lower quality of life. Since this condition is a complex problem, there is necessity to explore and determine various determinants from different levels. The aim of this systematic  review was to explore the acceptances of cancer treatments among cancer patients and its associated determinants. Articles published from 2010 to 2023 were searched in four databases: ScienceDirect, Medline, Google Scholar and PubMed. Articles written in English and focussing on three main cancer treatments (surgery, chemotherapy and radiotherapy) were eligible.  A narrative approach was used and the data were analysed into selected themes. Data suggest that several factors influence patient acceptance for cancer therapy including sociodemographic, economic and spiritual cultural backgrounds; patient knowledge and perceptions; community support, as well as policy and availability of health facilities.  The determinants consist of individual, interpersonal, institutional, community and public policy level and interaction between levels are contributing to cancer treatment acceptance. In conclusion, cancer treatment acceptance remains a problem in particular in low middle income countries. In addition, the data on radiotherapy referral acceptance were limited and needed further study.